The Synthesis of TiO2/PDMS Composites as Antibacterial Coatings on Cotton Fabrics - Priyadi, Rizki Feby Gardika; Wahyuni, Sri (Universitas Negeri Semarang, 2021)
Antibacterial properties on a substrate surface can occur due to two mechanisms, photocatalytic mechanism and the hydrophobic mechanism. Titanium dioksida (TiO2) is a material that has photocatalytic properties and polydimethylsiloxane (PDMS) is a material that is hydrophobic. TiO2 can be modified with PDMS to produce antibacterial materials. This modification can be done by compositing TiO2 and PDMS. The aim of the study was to determine the effect of TiO2/PDMS composites on the antibacterial properties of the coated cotton fabric on the surface. TiO2/PDMS composites were synthesized using the sonication method. The results of XRD analysis of TiO2 showed that TiO2 was crystalline with an anatase phase and had an average crystal size of 31.24 nm. The results of the FTIR analysis showed that Si–O–Ti vibrations appeared at a wave number of 874.53 cm-1 which indicated the formation of bonds between TiO2 and PDMS. TiO2/PDMS composites were coated on the surface of cotton fabrics by the dip-coating method. The results of the hydrophobic test showed that the largest contact angle was produced by the TiO2/PDMS composites coated fabric with a ratio of 1:2. The hydrophobic nature contributes to not getting wet easily on cotton fabrics, thereby reducing moisture which can prevent the growth of bacteria on the fabric. The results of the antibacterial test showed that the composites had an inhibitory effect on S. aureus bacteria. The UV irradiated TiO2/PDMS composite provided a larger diameter of inhibition zone. The diameter of the largest inhibition zone in the TiO2/PDMS composite coated fabric with a ratio of 2:1.